Please don't call me RI anymore; I may not be the one you think I am! - Lerolle, Nicolas (BioMed Central, 2012)
The previous issue of Critical Care reports new data on renal resistive index in critically ill patients. Although high renal resistive index may indeed be associated with acute kidney injury, the existence of several determinants of this index, of which renal resistance is only one among many, obscures the usefulness of this index in clinical practice.